Medulloblastoma in a Child with Fragile X Syndrome - Alexiou, George A.; Siozos, George; Stefanaki, Kalliopi; Vlachakis, Eustathios; Sfakianos, George; Prodromou, Neofytos; Moschovi, Maria (Neuropediatrics, 2012)
Fragile X syndrome is the most common cause of inherited intellectual impairment and has been associated with decreased incidence of cancer. We present the case of an 11-year-old boy with a diagnosis of fragile X syndrome who presented with gait imbalance, headache, and episodes of vomiting. Radiological investigation revealed the presence of a posterior fossa tumor. The patient was operated upon and the tumor proved to be a medulloblastoma (MB). To the best of our knowledge this is the first reported case of MB in a child with fragile X syndrome.
Keywords: medulloblastoma; fragile X syndrome; children